Development of Genially-Based SERABB Interactive Learning Media to Enhance Students’ Independence and IPAS Learning Outcomes in Elementary Education - Fajriati, Nurul; Rusdiyani, Isti; Fatimah, Atin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop Genially-based SERABB (Seru Eksplorasi Ragam Budaya Banten) interactive learning media to improve students’ learning independence and IPAS learning outcomes. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 30 fifth-grade students at SD Negeri Kewunen, Banten Province, Indonesia, who participated in the implementation stage. Data were collected through observations, interviews, documentation, questionnaires, and pretest–posttest learning outcome assessments. Data analysis was conducted using both qualitative and quantitative approaches. The validation results indicate that the media has a very high level of feasibility, with scores of 88% from media experts and 91% from material experts. The implementation results show a high level of student learning independence across aspects of self-confidence, responsibility, discipline, activeness, and learning motivation. In addition, the SERABB interactive media was found to be effective in improving students’ learning outcomes, as indicated by higher posttest scores compared to pretest scores, with an average N-gain of 0.76 and a significance value of p < 0.05. The media is equipped with interactive features such as animations, audio, quizzes, and independent exploration activities, which enhance student engagement in learning. Therefore, this study concludes that the SERABB media is valid, practical, and effective, demonstrating that cloud-based interactive media can serve as a strategic solution for integrating ethno-pedagogy into the elementary school curriculum.